Dimensional accuracy of a condensation silicone: comparison of storage time and measurement method - Bandoli Monteiro, Jaiane (2018)
Objective: This study aims to calculate the dimensional change of a condensation silicone through different measuring instruments (digital paquimeter, stereomicroscope and 3D coordinate measuring machine); in four separate times. Methods: In the experimental in vitro study four impressions of condensation silicone (Speedex) were performed with a specific device with four-time distances, resulting in sixteen measurements with each instrument. The pre-determinated times for measurement were: immediately after the impression (T0), after 30 min (T1), after 1 h (T2) and after 7 days (T3) of impression. The averages and standard deviations of measurements were submitted to analysis of variance and Tukey’s test, with significance level of 0.05. Results: The average (mm) for the samples measured with a digital paquimeter (T0= 5.82; T1 y T2= 5.80; T3= 5.78) and 3D coordinate measuring machine (T0= 5.75; T1=5.78; T2 y T3 = 5.77), there was a significant difference of dimension for the initial values in relation of values after 7 days (p = 0.037; p = 0.013, respectively), the same did not happen for the use of the stereomicroscope (T0, T1 y T3= 5.83; y T2= 5.81), that presented statistic similarity for all evaluated times (p = 0.754). Conclusions: The measurement method was the relevant factor that influenced the results of the dimensions of the impressions, the four times were not relevant in the dimensional changes of the silicon of condensation analyzed.